Applications of the Metatheory of Resilience and Resiliency in Rehabilitation and Medicine - Richardson, Glenn E. (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2011)
This presentation will based upon the “Metatheory of Resilience and Resiliency” which was described in the 2002 issue of the Journal of Clinical Psychology. The techniques that are applicable to health care providers are adaptations from the Personal Resiliency Training Guidebooks.DescriptionThe theoretical model of resiliency will be explained as a process—a personal journey through disruption and reintegration. The model will demonstrate the incremental process and series of choices evident in progression toward optimal health. The key stage in the re-occurring model is the trough of disruption. It is in chaos and the discomfort of leaving homeostasis that helping professionals can facilitate the experience of digging through superficial protective layers of consciousness to discover innate resilience. Resilience is a progressive force within everyone that drives them to maximize, embrace, and fulfill potentials. In most individuals, resilience is the drive to be in harmony with a source of energy beyond themselves. Techniques to facilitate the discovery of essential, character, noble, synergistic, ecological, universal, and orchestrational resilience for health practitioners will be described.